Pengaruh Program Sapta Pesona dan Fasilitas Terhadap Tingkat Kunjungan Wisatawan di Objek Wisata Goa Ergendang - Enjelina Sundari Br Bangun; Dewi Shinta Wulandari Lubis (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to determine the effect of the Sapta Pesona Program on the level of tourist visits to Ergendang Cave. Data collection techniques used in this study are: observation, interviews, and questionnaires. After all the data is obtained then the data uses spss 28.0. From the results of testing the data that has been processed, the first termination coefficient is 0.227 or 2.7%, indicating that the saptapesona and facilities variables are able to express variations in the number of tourist visits to the Ergendang Cave tourist attraction. The two Sapta Pesona variables have a partial effect on tourist visits, the facility variable has a positive effect on the number of visitors to the Ergendang Cave tourist attraction and is partially significant. The three charms and facilities in the Ergendang Cave also increase the number of visitors.